2017
DOI: 10.7763/ijcte.2017.v9.1175
|View full text |Cite
|
Sign up to set email alerts
|

An Empirical Study on Usability of Online Hotel Reservation Websites

Abstract: Abstract-With the popularity of the websites, online business can generate more benefit and possibly be success rapidly. One key success factor is the usability of the websites. Three quality characteristic factors based on usability are investigated, i.e., user experience, functionality and user interface usability. User experience concerns with aesthetic attributes, functionality checks for the appropriate functions, and user interface usability focuses on a good UI design or easy-to-use website. Furthermore… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 6 publications
0
1
0
Order By: Relevance
“…As the world becomes increasingly digitized, more and more individuals are turning to online business as a means to achieve financial success. (Sriphaew & Katkaeo, 2017) However, research suggests that age may be a determining factor in online business success (Meng et al, 2018). A study conducted by the Pew Research Center found that younger individuals are more likely to engage in online commerce than older ones (Pew Research Center).…”
Section: Agementioning
confidence: 99%
“…As the world becomes increasingly digitized, more and more individuals are turning to online business as a means to achieve financial success. (Sriphaew & Katkaeo, 2017) However, research suggests that age may be a determining factor in online business success (Meng et al, 2018). A study conducted by the Pew Research Center found that younger individuals are more likely to engage in online commerce than older ones (Pew Research Center).…”
Section: Agementioning
confidence: 99%